PENGARUH POLA ASUH ORANG TUA TERHADAP KONSUMSI ULTRA PROCESSED FOOD DAN KUALITAS GIZI PADA GENERASI ALPHA: TINJAUAN ISLAM DAN KESEHATAN - Anne Rufaidah; Anita Dewi Septiani; Yolanda Rahma Alodia; Hilman Taufiq Abdillah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This study analyzes the influence of parenting patterns on ultra-processed food (UPF) consumption and nutritional quality in Generation Alpha children aged 7-15 years from an Islamic and health perspective. An explanatory quantitative approach with purposive sampling was used, collecting data from 100 parent respondents in Bandung City via a Likert scale questionnaire analyzed with IBM SPSS version 26. Validity testing produced 19 of 20 valid items. Reliability testing showed Cronbach's Alpha > 0.70 for all variables. Normality testing (Kolmogorov-Smirnov) showed non-normal distribution (Sig. < 0.05), so Spearman correlation was employed. Results showed parenting had a significant negative effect on UPF consumption (r = -0.465, p < 0.001) and a significant positive effect on nutritional quality (r = 0.711, p < 0.001). Discussion integrates Kohlberg's moral development theory and Ulwan's Tarbiyatul Aulad fi al-Islam framework, affirming that positive parenting grounded in modeling, habituation, and supervision effectively reduces UPF consumption while improving nutritional quality in line with halal-thayyib principles.